2017
DOI: 10.1038/srep41001
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating orbital angular momentum of light with tailored in-plane polarization states

Abstract: Generally, polarization and phase are considered as two relatively independent parameters of light, and show little interaction when a light propagates in a homogeneous and isotropic medium. Here, we reveal that orbital angular momentum (OAM) of an optical vortex beam can be modulated by specially-tailored locally linear polarization states of light under a tightly-focusing conditon. We perform both theoretical and experimental studies of this interaction between vortex phase and vector polarization, and find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…In the monochromatic field limit, the fields in Eqs. (7) and (8) and the resulting Poynting vector can be approximated further as explained in Appendix B. This approximation allows us to perform the integrations in Eqs.…”
Section: B Linear Polarizationmentioning
confidence: 99%
“…In the monochromatic field limit, the fields in Eqs. (7) and (8) and the resulting Poynting vector can be approximated further as explained in Appendix B. This approximation allows us to perform the integrations in Eqs.…”
Section: B Linear Polarizationmentioning
confidence: 99%
“…The efficiency, on the other hand, can be enhanced by using heralded single photon source or post selections. We note that non-perfect technical issues, such as nonparaxial conditions and the nonuniform spatial profile of an LG beam for multiply-stacked rings, compromise either the fidelity or efficiency of HPI state preparation, but can still be optimized by, for instance, using beams with a longer Rayleigh range or equivalently larger beam waist and by optimizing the alignment 64 .…”
Section: Helical-phase-imprinted Subradiant Statesmentioning
confidence: 99%
“…Finally we study the scattering properties from the radially and azimuthally polarized excitations 64 , which allows us to further manipulate the local orientations of the atomic dipoles. The resonant dipole-dipole interactions in equations ( 11 ) and ( 12 ) can be straightforwardly generalized by replacing the term [1 − ] with [ ] and correspondingly the term [1 − ] with [ ].…”
Section: Light Scattering From Hpi Subradiant Statesmentioning
confidence: 99%
“…The momentum and angular momentum of light continue to be subject of intense research as demonstrated by recent investigations of these quantities in vacuum, 1,2 in photonic materials, [3][4][5][6] in the near-field regime, [7][8][9][10] and also in the quantum domain. 11 In the case of continuous media, the experiments studying the momentum transfer between the electromagnetic field and the medium have mainly focused on the interaction of light with liquids.…”
Section: Introductionmentioning
confidence: 99%